The Influence Perception Fund Quality Risk Health Services Against Interest in Using KB acceptor - Aminatu Juhria; Hawignyo Hawignyo (LPPM Universitas Buddhi Dharma, 2023)
Study This aim For test And analyze about Influence Perceptions of Risk and Quality of Health Services Against Interest in Using KB acceptors at KB acceptors at Mandiri Midwife Practice Rina Listiana Karawang. This research was conducted using descriptive and verification methods, that is: gather, serve, analyze And do testing hypothesis, make conclusion And suggestion. Sample collected with using the Slovin method and non-probability sampling techniques with Engineering Sampling Purposive Sampling. With a total sample of 361 from a population of 3684 person. engineering analysis Which used that is technique analysis range scale And analysis track with help Methodof successful intervals (MSI), program computer MicrosoftExcel 2010, Microsoft Word 2010 and applications SPSS version 23 . Based on the results of the analysis that has been carried out this study proves that . The correlation coefficient between the variables Perceived Risk and Quality Service Health obtained mark as big 0.875 Which means have level correlation Which Very Strong, positive And significant between Perception Risk And Quality service health. Influence in a manner Partial Perception Risk to Interest Use as big 0.328 And Quality Service Health Which value of 0.525. So it can be stated that the Quality of Health Services is more Lots give contribution to Performance Interest Use acceptor KB compared to with Perception Risk. Influence simultaneous Quality Service Health And Perception Risk to Interest Use as big 85.3% whereas the remaining 14.7% is a variable other who does not researched.